Improvement of Skin Wound Healing for Diabetic Mice with Thermosensitive Hydrogel Combined with Insulin Injection - Lingling Fang; Haijian Wu; Xiaoyan Li; Jianghua Fang; Yabin Zhu (International Journal of Endocrinology)
Chronic skin wound caused by diabetic disease is very common worldwide. Moreover, there is a shortage of effective curing technology in clinic. In this work, we developed a novel technology using thermosensitive hydrogel on wound top combined with insulin injection. The efficiency and mechanism of this technology were investigated in a diabetic mouse model. Dorsal-paired 8–10 mm diameter wounds were created in 12 mice. The wound healing rate was determined over a 28-day interval in healthy control (Control), control with diabetes (DControl), poloxamer treatment (Pox), and poloxamer plus insulin injection (Poxin) mice. Histological specimens were observed in all samples. Real-time quantitative polymerase chain reaction (qRT-PCR) was performed to measure the relative expression of α-smooth muscle actin (α-SMA) and transforming growth factor beta 1 (TGF-β1) in wound tissues at 7, 14, and 28 days. Compared with DControl animals, those treated with Poxin showed accelerated wound closure and healing rate (p < 0.05); expression of both α-SMA and TGF-β1 was significantly higher than that of the DControl and Pox animals during the first 7 days postoperation, but a significant decrease at day 14. Therefore, we concluded that hydrogel combined with insulin accelerated wound healing. Controlling the glucose level via insulin injection is more beneficial than hydrogel alone for healing chronic wounds, potentially through the increase of α-SMA and TGF-β1 expression in early phase.